1966
DOI: 10.1073/pnas.56.3.979
|View full text |Cite
|
Sign up to set email alerts
|

The nitrogenase system from Azotobacter: two-enzyme requirement for N2 reduction, ATP-dependent H2 evolution, and ATP hydrolysis.

Abstract: The requirement for both an electron donor and ATP for the enzymatic reduction of N2 to ammonia was demonstrated with extracts of Clostridium pasteurianum,1-4 Azotobacter vinelandii,5 7 and Rhodospirillum rubrum.' 8 With hydrosulfite as the electron donor and an ATP-generating system (creatine phosphokinase), N2-reducing preparations from A. vinelandii and R. rubrum were shown to catalyze a concomitant ATP-dependent H2-evolution reaction.6-9 This reaction was subsequently demonstrated with extracts of C. paste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
164
0
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(168 citation statements)
references
References 13 publications
3
164
0
1
Order By: Relevance
“…However, genetic studies indicate that neither NrfA nor NrfH is required for Fe(III) reduction by G. sulfurreducens (Table 5). It should also be considered that this increased expression of nrfA and nrfH may be related to nutrient limitation associated with the Fe(III) oxide medium, as increased expression of NrfA and NrfH has been associated with nitrogen limitation (Bulen & LeComte, 1966;Hageman & Burris, 1978).…”
Section: Electron Transport Genes Only Upregulated In Fe(iii) Oxide-gmentioning
confidence: 99%
“…However, genetic studies indicate that neither NrfA nor NrfH is required for Fe(III) reduction by G. sulfurreducens (Table 5). It should also be considered that this increased expression of nrfA and nrfH may be related to nutrient limitation associated with the Fe(III) oxide medium, as increased expression of NrfA and NrfH has been associated with nitrogen limitation (Bulen & LeComte, 1966;Hageman & Burris, 1978).…”
Section: Electron Transport Genes Only Upregulated In Fe(iii) Oxide-gmentioning
confidence: 99%
“…Although increased expression of proteins involved in nitrogen fixation is frequently associated with nitrogen limitation (Bulen and LeComte, 1966;Hageman and Burris, 1978), studies have also shown that under conditions of nitrogen limitation, nitrite reductases can be involved in the anabolic incorporation of nitrogen into biomolecules Nakano et al, 1998). Therefore, it is possible that the increased expression of the nitrite reductase genes, nrfA and nrfH, in sedimentgrown cells is the result of nitrogen limitation.…”
Section: Fixed Nitrogen and Phosphorous Limitation During Growth In Smentioning
confidence: 99%
“…In 1966 Bulen and Le Comte [30] found in their purified nitrogenase preparations ((242-1) a pinkish protein fraction, that could be separated from the nitrogenase proteins by DEAE-cellulose chromatography. The fraction could be eluted from the column with 0.15 M NaCI.…”
Section: Purijiication Of Iron-sulfur Protein II From Preparation C42mentioning
confidence: 99%